PELATIHAN PEMBUATAN ALAT PERAGA MATEMATIKA UNTUK SEKOLAH DASAR MEMANFAATKAN BAHAN BEKAS DI SD NEGERI 01 PADANG AIR DINGIN - Mirda Swetherly Nurva; Tiara Fikriani (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
The object of mathematics is abstract, so that the math teacher must compose abstract mathematical objects to be easy learning for students. Solving this problem, experience through real objects (concrete) such as props is required. Using props, students can see, feel, and think directly about the object after they learn so that the abstract concept being studied can settle, cling, and last in the student's mind. This devotion aims to provide the ability to think mathematics creatively and develop a favourable attitude towards mathematical thinking. The methods of this devotional activity are lectures, Q&A and discussions. The results obtained after doing this activity have an impact on students' understanding. Students who understand the materials taught faster and then teachers are also more creative in utilizing used materials to learn media. Teachers do not have to spend much money to make an attractive prop